Religious experience and schizophrenia in modern man : an experiential theoretical study - Borchardt, Frederick Francois (Rhodes University, Faculty of Humanities, Department of Psychology, 1990)
In this study the psychological structures of two categories of religious and schizophrenic experience were examined from a phenomenological- existential perspective. Existing theories describe schizophrenia as an unfree, rigid experience with limited possibilities for selfhood. Some theorists believe, however, that some forms of schizophrenia can be seen as potential growth experiences which could facilitate existential renewal. These forms of schizophrenia are mystical, mythical or spiritual in nature. Religious experiences are, according to the literature, essentially renewal experiences facilitating existential growth and transformation through a particular system of thought and devotional relationship shared by a group of people. The Duquesne phenomenological- psychological method was used to analyse seven case studies, four of which involved schizophrenic experiences and three which involved religious conversion experiences. The general psychological structure which emerged through this analysis showed both schizophrenia and religious experience to have specific implications for the personal, social, material and mystical dimensions of being. The description of a specific psychological structure of experience which could optimally facilitate existential growth and transformation was attained by examining psychological structures where the subject's experience culminated in existential growth and transformation (such as religious experience and certain schizophrenIc experiences). As both these categories of experience displayed a strong mystical component, a psychological structure of experience which facilitates a transformative mystical experience was described. It can be concluded that an experience involving a mystical dimension could be transformative if the general psychological structure of the person displays (a) an openness towards reality as it presents itself (b) an experience of oneself as having a measure of existential freedom (c) a certain sense of security in one's own selfhood and (d) a social world which could understand, support and reflect inner experiences.
Keywords: Schizophrenia -- Religious aspects; Experience (Religion) -- Psychological aspects